Early Communication Skills and Special Education Outcomes at School Entry: Implications for Pediatric Care and Screening - Matthew H. Kim PhD; Laura Lee McIntyre PhD (SAGE Publishing, 2019)
Objective . To examine whether children's early communication skills at age 3 predict special education outcomes at kindergarten entry. Methods . Data from 139 children eligible for early intervention or early childhood special education services were examined. Early communication was defined separately as expressive and receptive language skills and was measured by the Vineland Adaptive Behavior Scales-Second Edition. Outcome variables were parent-reported measures of special education use and dosage as well as speech therapy receipt and dosage at kindergarten entry. Results . Better expressive language skills at age 3-but not receptive language skills-predicted a significantly reduced likelihood (odds ratio = 0.79) of receiving speech therapy at kindergarten entry. There were no effects of early communication on broader receipt of special education services as well as on special education dosage. Conclusions . Screening of specific domains of early communication skills during routine pediatric care, in conjunction with the evaluations of other professionals involved in the child's education and health, might be an effective method for identifying children who are likely to receive speech therapy and other special education services at kindergarten entry.